Èquations aux dérivées fractionnaires : Propriétés et applications - Zineddin Zeroual (My University, 2025)
In this memory, we are interested in fractional differential equations. We began by studying a time-space fractional differential equation with a nonlinearity of exponential growth . Then we study an integro-differential diffusion equation. More precisely, the local existence and uniqueness of solutions are demonstrated. Furthermore, we prove that the solution blows up in finite time, and we provide an estimate of the blow-up time. The proofs are based on the Banach fixed point theorem and also on the appropriate choice of the test function in the weak formulation of the problem. ------------------------------------------------------------------------------------ في هذه المذكرة، لقد اهتممنا بالمعادلات التفاضلية الكسرية. بدأنا بدراسة معادلة تفاضلية كسرية بالنسبة للزمان والمكان مع لاخطية ذات تزايد أسي. بعد ذلك، قمنا بدراسة معادلة انتشار تكاملية- تفاضلية. و بشكل أدق، تم إثبات الوجود المحلي ووحدانية الحلول. علاوة على ذلك، اثبتنا أن الحل ينفجر في زمن منتهٍ، و قدمنا تقديرًا لزمن الانفجار. تعتمد البراهين بشكل أساسي على مبرهنة النقطة الثابتة لباناخ، وكذلك على الاختيار المناسب لدالة الاختبار في الصياغة الضعيفة للمشكل. ------------------------------------------------------------------------------------ Dans ce mémoire, nous nous sommes intéressés aux équations différentielles fractionnaires. Nous avons commencé par l’étude d’une équation différentielle fractionnaire en temps et en espace avec une nonlinéarité de croissance exponentielle. Ensuite, nous avons étudié une équation de diffusion intégro-différentielle. Plus exactement, l’existence locale et l’unicité des solutions sont démontrées. De plus, nous montrons que la solution explose en temps fini et nous donnons une estimation du temps d’explosion de la solution. Les démonstrations reposent essentiellement sur le théorème de point fixe de Banach, et aussi sur le choix convenable de la fonction test dans la formulation faible du problème.
Keywords: Fractional calculus; fractional derivative; fractional integral; local existence; explosion of solutions.; الحساب الكسري، الاشتقاق الكسري، التكامل الكسري، الوجود المحلي، انفجار الحلول.; Calcul fractionnaire; Dérivée fractionnaire; Intégrale fractionnaire; Existence locale; Explosion des solutions.